Marketing research on consumer behaviour and drinking habits of people living in Imatra - Lappeenranta region, Finland - Anttonen, Valeria (Saimaan ammattikorkeakoulu, 2017)
The aim of this bachelor’s thesis was to carry out a marketing research aimed to understand the customer behaviour and customer drinking habits in Imatra-Lappeenranta region. The author believed that some companies within catering industry operate without considering the essence of customer behaviour and their drinking habits. The research consisted of three different approaches for better analysing the topic in question: direct observation, on-line survey and in-depth interview. Direct observation included author’s seven years of experience and review on customer behaviour and drinking habits in Finland. On-line survey and in-depth interview included structured questions which, together with direct observation method, helped to understand the customer living or visiting the town of Imatra and Lappeenranta region. The bachelor’s thesis provided an informational base related to consumers’ behaviour and habits within catering industry of South Karelia. The author expressed personal suggestion for improvements in bar industry in Imatra and Lappeenranta. This thesis work can be used as analysis for product and service targeting towards specific customer segments.